Introductory Statistics with R - Dalgaard, Peter (Springer, 2008)
R is a statistical computer program made available through the Internet under the General Public License (GPL). That is, it is supplied with a licensethatallowsyoutouseitfreely,distributeit,orevensellit,aslongas the receiver has the same rights and the source code is freely available. It exists for Microsoft Windows XP or later, for a variety of Unix and Linux platforms, and for Apple Macintosh OS X. R provides an environment in which you can perform statistical analysis and produce graphics. It is actually a complete programming language, although that is only marginally described in this book. Here we content ourselves with learning the elementary concepts and seeing a number of cookbook examples. R is designed in such a way that it is always possible to do further computations on the results of a statistical procedure. Furthermore, the design for graphical presentation of data allows both no-nonsense methods, for example plot(x,y), and the possibility of ﬁne-grained control of the output’s appearance. The fact that R is based on a formal computer language gives it tremendous ﬂexibility. Other systems present simpler interfaces in terms of menus and forms, but often the apparent userfriendlinessturnsintoahindranceinthelongerrun.Althoughelementary statistics is often presented as a collection of ﬁxed procedures, analysis of moderately complex data requires ad hoc statistical model building, which makes the added ﬂexibility of R highly desirable.
Keywords: Statistical computer program